First detection of Klebsiella quasipneumoniae producing OXA-181 carbapenemase in Malaysia. Issue 10 (October 2020) - Lau, Min Yi; Ponnampalavanar, Sasheela; Lee, Way Seah; Jabar, Kartini Abdul; Chua, Kek Heng; Idris, Nuryana; Chong, Chun Wie; Yap, Polly Soo Xi; Teh, Cindy Shuan Ju
Abstract: The emergence of carbapenemase-producing Enterobacteriaceae has become a major global concern. OXA-48-like carbapenemase gene and its variants have been increasingly reported worldwide. This study reported the first OXA-181-producing Klebsiella quasipneumoniae isolate in Malaysia. This bacterium was isolated from blood specimen of a three-year-old boy with Alagille syndrome who had liver biopsy on October 2016. He had undergone liver transplant in India ten months previously. The genotypic and phenotypic characteristics of the strain were elucidated in this study. To our best knowledge, this is the first report of OXA-181-producing K. quasipneumoniae in Malaysia.